INCORPORAÇÃO DE ÓXIDO DE GRAFENO EM ARGAMASSA: ÁNALISE DA RESISTÊNCIA MECÂNICA À COMPRESSÃO (REMUNOM, 2024)
AbstractThis study investigates the influence of graphene oxide (GO) on the mechanical property of compressive strength of cement mortar, aiming to improve durability and strength requirements of construction materials and minimize the consequent waste of raw material, due to the high demand for cement, a factor that generates significant environmental impact. In this study, mortar specimens were produced with different dosages of GO, ranging from 0% to 0.5% in proportion to Portland High Initial Strength Cement (CP V-ARI). Axial compressive strength tests were performed at 14 and 28 days, with the results indicating a progressive increase in mechanical strength concomitant with the increase in the dosage of GO. The results suggest that GO may be a viable alternative to optimize the performance of mortars, expanding their use and durability in civil construction. However, further research is recommended to explore the application methods and the challenges associated with the production and incorporation of nanomaterials in cement matrices. Keywords: Nanomaterials; Cement mortar; Mechanical resistance.